THE EFFECT OF GIVING MORINGA-HONEY ON LEUCOCYTE AND TOTAL LYMPHOCYTE COUNT IN PREGNANT WOMEN IN MAROS DISTRICT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nutrition is one of the basic human needs required for energy, cell regeneration, and wound healing. This studyaimed to assess the effect of Moringa-Honey on leukocyte and Total Lymphocyte Count in Turikale and Lau Health Centers. Itwas a Randomized Controlled Trial with Pre and Post Double-Blind, examined the leukocyte and Total Lymphocyte Countconducted in the working area of the Turikale Public Health Center and Lau Public Health Center, Maros District, fromFebruary 3 to April 30, 2020. Based on purposive sampling, about 46 pregnant women were involved (24 respondents obtained5 ml/day of Moringa-Honey (MK) plus Fe Tablets; 22 respondents obtained 15 ml/day of Regular-Honey (MB) plus FeTablets) and intervention was every morning during 8 weeks. Data were analyzed using Paired T-Test and Independent SampleT-Test using SPSS version 26. There was a significant decrease in Leukocyte levels after the intervention in the Moringa-Honey and Regular-Honey groups, with the difference of 1225/μL and 1154/μL, respectively. The p-value of both groups was0.252 (α= 0.05), which indicated no significant difference between the two groups. However, the total lymphocyte count(TLC) in the two groups showed no changes occurred. The significant reduction in leukocyte levels in both groups and agreater slope was developed after consuming Moringa-Honey. There was no change in the total lymphocyte count in either theMoringa-Honey or Regular Honey groups